Investigation of Shallow Structures as The Pathway of Oil Seep in The Alue Punoe Village, Bireuen District, Aceh Province, Indonesia - . Asrillah; Muhammad Syukri; . Marwan; Fuad Akbar (Aceh International Journal of Science and Technology, 2016)
Measurement of magnetic data has been done in the area of oil seeps in the village of the Alue Punoe, with 121 measurement points as a grid within 500 m x 500 m area where each grid is approximately in 250 m2. The total magnetic field measurement has been examined by using Proton Precession Magnetometer (PPM). Upward continuation correction was applied to obtain residual magnetic field anomaly. Residual magnetic field anomaly data are mapped using the Surfer software, while subsurface models are made using the Mag2DC software. Based on the models that have been sliced from the local magnetic anomalies along the cross section of A-B and C-D from which then obtained a shallow structure which is a fault whose an approximate depth from 30 to 100 meters and three stratified media. The stratified media of the study area are interpreted as an alluvial deposit, alternating sandstone and clay and igneous rocks. Interpretation of subsurface models shows that there exists a shallow structure assumed as a fault. Expected fault has an adjacent to the manifestations which are about 50 to 70 m. It strengthens the case that the fault is strongly related to as the pathways of oil seepsfrom possibly existed petroleum system below subsurface of unknown strata